New role of extemporaneous manufacturing in regulating drug products access onto the market - A. V. Alekhin; T. N. Erivantseva; V. V. Ryazhenov; N. N. Lyskov; N. A. Alekhina; M. M. Kuznetsova (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2023)
The aim of the work was to study the legal aspects of the legislative regulation for manufacturing medicines in a pharmacy organization.Materials and methods. Databases of ConsultantPlus, Cyberleninka, Food and Drug Administration (FDA), European Medicines Agency (EMA), National Center for Biotechnology Information (NCBI), PubMed, e-library, WIPO Lex were used as search sources. The search was based on the following keywords and phrases: intellectual property, pharmacies+invention, patent, drugs, extemporal+production, orphan+diseases, as well as their Russian counterparts. 133 sources of information, including scientific articles and regulations, were found out; 50 have been included in this review. The analysis of information sources published from 2013 to 2023, was determined by the peculiarities of legislation changes in this area.Results. The article provided an overview of modern, including regulatory practice, pharmaceutical manufacturing in the Russian Federation, and also analyzed the benefits of this activity for the medical community, patients and the state. At the same time, the individualization of drug treatment has made it possible to work out systemic solutions for developing drug therapy methods for special groups of patients for whom the economic feasibility of a pharmaceutical registration and launching such drugs onto the market has been brought into challenge. In addition, pharmacy manufacturing is an accessible tool in the study of the drugs prescribed by a doctor not in accordance with the instructions for medical use (off-label) or in the dosage forms/dosages that are not on the market. Extemporaneous manufacturing can be also a part of the process of "repositioning" drugs on the market, subject to compliance with the requirements for pharmacy manufacturing and control of the prescribed drugs safety. The possibility of pharmaceutic drug manufacturing also makes it possible to partially resolve issues related to intellectual property. As a result of the carried out analysis, the following hypothesis was confirmed: the legislative changes have a similar legal assessment both in Russia and abroad and correspond to the legal practice in resolving intellectual property issues in relation to pharmacy organizations.Conclusion. The renewal of a pharmacy production will improve the availability of the drug care to the population, taking into account individual dosages and dosage forms in various therapeutic areas, and can also become a tool for repositioning drugs or clinical testing of new molecules for rare incurable diseases.